Mechanical behaviour of recycled plastic lumber as a structural material in ecodomes - López Chica, José Daniel
This study explores the potential of recycled plastic lumber as a structural material for construction to promote sustainable building practices. Although these materials offer ecological advantages and mechanical strength, their adoption faces challenges due to the lack of testing standards.  To evaluate their properties, tensile, compression, flexural, hardness, impact and volumetric density tests were conducted under controlled conditions, using a one-factorial experimental design with a standard recycled polymer mix. Twenty samples were used per test to ensure accuracy and reliability of the results. In addition, a prototype ecodome was designed, and structural analysis was carried out using SolidWorks simulations to calculate its strength under different loads.  The results suggest that the recycled plastic lumber exhibit adequate mechanical properties, although some variations were identified that point to possible areas for improvement in manufacturing homogeneity. Tests showed levels of tensile, hardness and compressive strength that demonstrate their viability to support structural loads..  Finally, recycled plastic lumber shows great potential for use in sustainable structural applications, supporting the reduction of plastic waste and promoting responsible use of resources in construction.